2010
DOI: 10.1111/j.1365-2575.2010.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trust, guanxi orientation and face on the intention of Chinese employees and managers to engage in peer-to-peer tacit and explicit knowledge sharing

Abstract: Knowledge sharing is recognised as one of the most critical components of knowledge management. Successful and efficient knowledge sharing could directly facilitate knowledge creation and so help a firm to maintain its competitive advantage. Consequently, identifying which factors could encourage or inhibit people to share knowledge is potentially of great value. In this study, we explore the impact of selected socio-cultural factors, viz. trust, guanxi orientation and face, on the intention to share explicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
169
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(180 citation statements)
references
References 49 publications
7
169
1
3
Order By: Relevance
“…Our results also showed that individuals with high-quality LMX had less intention to withhold knowledge, implying that knowledge withholding is one way team members respond to low-quality exchanges with their leaders [42]. To ensure the successful operation of a project team, a leader must create a fair and cohesive work environment in which group members are willing to identify with the project vision, participate in its implementation, and share their knowledge [75,76].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Our results also showed that individuals with high-quality LMX had less intention to withhold knowledge, implying that knowledge withholding is one way team members respond to low-quality exchanges with their leaders [42]. To ensure the successful operation of a project team, a leader must create a fair and cohesive work environment in which group members are willing to identify with the project vision, participate in its implementation, and share their knowledge [75,76].…”
mentioning
confidence: 95%
“…A second explanation may relate to contextual sensitivity. Participants were Taiwanese, and research has shown that guanxi (defined as "a relationship between two or more individuals that is implicitly based on reciprocity and mutual interest" [75]), an important sociocultural factor, plays a critical role in workers' information-sharing behaviors in Chinese culture [75,79,80]. Given that the effort-withholding framework we used is based on the work of Western scholars, we did not include guanxi in our model.…”
mentioning
confidence: 99%
“…Besides construct validity, discriminant validity and convergent reliability also needed to be evaluated. Average variance extracted (AVE) is a significant parameter for assessing discriminant validity and calculating composite reliability (CR) to assess convergent reliability [53][54]. Table 3 shows the mean, standard deviation (SD), CR and AVE, and Table 4 shows the correlations between each two constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the model constructs examined in this study. Figure 1 illustrates the research model and hypothesized relationships derived from the original study (Huang et al, 2011).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…We choose to answer these questions not with a new study, but by replicating work originally done in China that explores the intention to share tacit and explicit knowledge as a result of Guanxi orientation, face, and trust. We conduct a methodological replication study of The impact of trust, Guanxi orientation and face on the intention of Chinese employees and managers to engage in peer-to-peer tacit and explicit knowledge sharing (Huang et al, 2011). We undertake this replication to determine which aspects of Chinese business orientation (i.e.…”
Section: Introductionmentioning
confidence: 99%